ARAHAN PERANCANGAN TAMAN CATUR KOTA PONTIANAK MENJADI RUANG PUBLIK TERPADU RAMAH ANAK - Febrianti, Cindy; Zain, Zairin; Br Gultom, Bontor Jumaylinda (JMARS: Jurnal Mosaik Arsitektur, 2025)
Child-Friendly Integrated Public Space, hereinafter referred to as RPTRA, is the idea of a public space consisting of parks that have interesting play equipment, CCTV, and areas that serve the needs of the surrounding community. As an urban park that serves as a RPTRA, Taman Catur should use child-friendly designs because if the facilities of the RPTRA are not carefully designed, they can be very dangerous. The research method used is a qualitative method with a descriptive analytical approach to present the existing conditions of the Taman Catur facilities, the ideal conditions of an RPTRA, and design guidelines to ensure the park meets RPTRA criteria. The purpose of this research is to produce a design direction for Taman Catur in order to match the criteria of RPTRA in accordance with the theory of Baskara (2011), SNI 9169: 2023 on Child Friendly Play Space, and Pontianak City Regional Regulation Number 1 Article 11 Year 2022 on Child Friendly City. The research results also indicate that the areas in Taman Catur do not meet the RPTRA criteria and require the addition or removal of existing supporting facilities. Deficiencies that exist in Taman Catur include aspects of safety, health, and ease of accessibility.